KEARIFAN LOKAL DALAM PEMBANGUNAN KOMPLEKS CANDI GUNUNG KAWI - A.A Gde Bagus; Hedwi Prihatmoko (Balai Arkeologi Bali, 2016)
Gunung Kawi Temple is one of the most monumental archaeological remains in Bali, originating from the 10th to 11th century. This study aims to determine the values of local wisdom of ancient Balinese society related to the construction and presence of Gunung Kawi Temple. Data were collected through literature study and observation. Analysis was conducted through qualitative approach using data integration and explanation based on theory. Explanation is presented in narrative text. The results of this study indicate that the construction using the concept of cliff temple is an adaptation to address the limitations of geographical features and material resources. This adaptation is a form of ancient Balinese society local wisdom. This local wisdom is also reflected on the environmental preservation value which is related to the function of Gunung Kawi Temple as a religious sacred building. Kompleks Candi Gunung Kawi merupakan salah satu tinggalan arkeologi paling monumental di Bali yang berasal dari abad ke-10 sampai 11 Masehi. Kajian ini bertujuan untuk mengetahui nilainilai kearifan lokal masyarakat Bali Kuno yang terkait dengan pembangunan dan keberadaan Kompleks Candi Gunung Kawi. Pengumpulan data dilakukan melalui studi kepustakaan dan observasi. Analisis dilakukan melalui pendekatan kualitatif dengan pengintegrasian data dan memaparkan simpulan-simpulan berdasarkan teori. Pembahasan kemudian disajikan dalam bentuk teks naratif. Hasil kajian ini menunjukkan bahwa pembangunan dengan konsep candi tebing merupakan bentuk adaptasi dalam menyikapi keterbatasan geografi dan sumber bahan baku. Adaptasi tersebut merupakan salah satu wujud kearifan lokal masyarakat Bali Kuno. Kearifan lokal tercermin juga dari nilai pelestarian lingkungan yang terkait dengan fungsi Kompleks Candi Gunung Kawi sebagai bangunan suci keagamaan.